Ethno-Pragmatic Study of Sam Ukalaâ€™s The Slave Wife and The Placenta of Death - Maledo, Anita Erhuvwu (NIU Journal of Humanities; Vol. 5 Núm. 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
This paper is an ethno-pragmatic study of proverbs in Sam Ukala’s The Slave Wife (1982) and The Placenta of Death (2007) in the face of the paucity of linguistic studies of the plays of Sam Ukala . It applies Brown and Levinson’s (1987) politeness theory with insights from Dell Hymes’ ethnography of communication. The focus is to explain how politeness features are appropriated to guide the usage of proverbs in the selected plays, while paying attention to the ethnographic features of the usage of proverbs. Ten proverbs are purposefullly selected from the texts for a rigorous and qualitative analysis. Findings show that the politeness routines and the ethnographic features of speaking appropriately guide the usage of proverbs in the socio-cultural context of the plays and they ensure that there is no breakdown in communication. Specifically, the politeness features inherent in the proverbs are face saving devices (though some proverbs contain face threatening acts) as they help to ease tensions in their mitigating roles while Dell Hymes’ speaking demonstrates that the use of proverbs in the texts obeys the social-cultural norms of interaction of Owa people. Finally, the paper shows the relevance of the place of linguistics in the study of the plays of Sam Ukala. Keywords : Politeness, Proverbs, Sam Ukala, Ethnograpy of Speaking